Exploring causes of delays in help-seeking behaviours among symptomatic Omani women diagnosed with late-stage breast cancer - A qualitative study. (December 2022) - Al-Azri, Mohammed; Al-Awaisi, Huda
Abstract: Purpose: Breast cancer (BC) is the most commonly diagnosed cancer in Oman; however, the majority of women are diagnosed at a relatively young age and late stage. Delays in BC diagnosis may be attributable to patient-related barriers to medical help-seeking, such as embarrassment arising from breast examinations or negative perceptions of cancer or a cancer diagnosis. Identifying and addressing patients-related barriers to medical help-seeking may help early BC detection, increase the survival rate, and improve prognosis. This study aimed to explore causes of delays in medical help-seeking behaviours among symptomatic Omani women diagnosed with late-stage BC. Methods: Purposeful sampling was used to identify Omani women diagnosed with late-stage BC (i.e., stages III or IV) at the two main referral oncology centres in Oman. Semi-structured individual interviews were utilised to collect data regarding the participants' reasons for delaying seeking medical help. The qualitative framework analysis approach was used for data analysis. Results: A total of 17 women participated in the study. The mean age was 41.94 ± 7.87 years (range: 27–56 years). Six reasons for delays in seeking medical help were identified, including: (1) Being in denial of BC symptoms; (2) normalisation of BC symptoms attributed to hormonal changes, dietary changes, or work-induced stress; (3) misinterpretation of BC symptoms attributed to other diseases or expectation of more alarming/obvious BC symptoms; (4) pursuit of alternative medicine remedies; (5) false reassurance or incorrect advice from family members or friends; and (6) practical barriers, such as childcare responsibilities and lack of access to transport. Conclusion: Several reasons were identified for delays in seeking medical help for BC symptoms, including cultural and emotional factors and a lack of knowledge of BC symptoms. Increased awareness of BC symptoms and a better understanding of Omani women's beliefs, cultures, and behaviours may help to reduce delays in BC presentation and diagnosis. Highlights: Omani women reported several distinct reasons for delays in seeking medical help during the appraisal of BC symptoms. Being in denial and the normalisation and misinterpretation of BC symptoms were common reasons for delays in seeking medical help. There is an urgent need to develop educational interventions strategies to encourage women to seek early medical help for BC symptoms. Health care physicians should provide additional emotional support and consider behaviour modification for Omani BC patients.